Dissimilar metals TIG welding-brazing of AZ31 magnesium alloy to 304 stainless steel. (2021) - Kotari, Sairam; Punna, Eshwaraiah; Gangadhar, S.M.; Cheepu, Muralimohan; Sarkar, P.; Venukumar, S.
Abstract: TIG welding-brazing of dissimilar metals magnesium alloy to stainless steel was investigated, and the wettability and spreadability of magnesium based filler metal on the stainless steel surface were analyzed. The microstructures of welded samples were observed using optical microscope and scanning electron microscopy (SEM). The microhardness at the weld interfaces found to be higher than the substrates owing to the presence of MgAl2 and MgO intermetallic compounds. The maximum tensile strength of the weld joints was about 69 MPa, and the tensile fracture occurred at heat affected zone on weak material of the magnesium side and/or at stainless steel/weld seam interface along intermetallic layer. The fracture surface was analysed by using SEM analysis. The ductile mode of fracture was observed with the formation of voids.